Pelanggaran Kode Etik Dewan Perwakilan Rakyat saat Rapat - Riezkiana, Frieshella Ananda; Faiz, Muhammad; Saputra, Indra; Sapitri, Roni; Safira, Nazwa; Ritonga, Fashya Syahrani; Syahputra, Muhammad Vischal (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Violation of the code of ethics in the House of Representatives (DPR) can include various things, ranging from inappropriate language, unethical behavior, self-interest conflicts, to violations of meeting procedures. The most common violations that occur during DPR meetings are unethical behavior that violates the legislative institution's code of ethics, creating an unprofessional environment. This research aims to identify and analyze the competencies of DPR members in carrying out their duties, as well as the characteristics of a council that is in line with the principles of Pancasila. The type of research used is Normative Juridical Legal Research. The results of this research can intervene in the behaviors of DPR members during meetings. Law enforcement agencies should be able to defend themselves from external interventions and be firmer in resolving issues and violations of the code of ethics by DPR members.